Crise environnementale et santé mentale : nouveaux enjeux épistémiques, nouvelles approches - Guernut Mathilde; Baleige Antoine (Amnis)
The structural changes in our social organization in response to the contemporary environmental crisis are leading to a transformation of our social organizations. In order to face their health impact, developing new knowledge and approaches is necessary. Because changes in the socio-cultural context modify the ideological frameworks upon which we build our knowledge, developing new approaches requires an epistemic redefinition. In order not to reproduce erroneous thought patterns, it is necessary to define the ideological frameworks at work and to anticipate their transposability in a society conceived as sustainable. In this paper, we present the three main ideologies of contemporary Western mental health and successively question their compatibility with the establishment of a sustainable society, social transformations to come and their impact on the production and transmission of knowledge. In addition to the development of new, fairer and more equitable inclusive approaches, responding to the environmental issue in mental health requires a change in power dynamics to the benefit of users/survivors of mental health.